Analisis Implementasi Quality of Work Life (QWL) dalam Manajemen Sumber Daya Manusia di Sekolah - Nasri Dini, Muhammad; Makruf, Imam; Wulandari, Fitri (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
Islamic Education Institutions must always improve their human resources. One of them is by implementing Quality of work life. This research will analyze the implementation of Quality of work life in human resource management in schools. This article was written using qualitative methods. The data source was obtained from the results of a case study from an educational institution, SMP Muhammadiyah Imam Syuhodo. The data collection methods used by the author are participatory observation, interviews and documentation. Participatory observation is observation carried out by researchers by observing and participating directly in the lives of the informants being researched. The data analysis method used is by collecting and reducing data. The conclusion of this research shows that Muhammadiyah Imam Syuhodo Middle School has tried to implement the principles of Quality of work life within its institution. Although it has not been implemented perfectly. The implication of the research above is that the implementation of Quality of Work Life at SMP Muhammadiyah Imam Syuhodo can serve as a model for improving human resource management in other Islamic educational institutions.